1984
DOI: 10.1128/mcb.4.4.642
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biosynthesis of diphthamide, studied with mutant Chinese hamster ovary cells resistant to diphtheria toxin.

Abstract: Diphthamide, a unique amino acid, is a post-translational derivative of histidine that exists in protein synthesis elongation factor 2 at the site of diphtheria toxin-catalyzed ADP-ribosylation of elongation factor 2. We investigated steps in the biosynthesis of diphthamide with mutants of Chinese hamster ovary cells that were altered in different steps of this complex post-translational modification. Biochemical evidence indicates that this modification requires a minimum of three steps, two of which we accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 14 publications
1
75
1
Order By: Relevance
“…BLAST search indicated that YLR143W is conserved in both eukaryotes and archaea, but not in bacteria, similar to other proteins involved in diphthamide biosynthesis. The human ortholog is ATP-binding domain-containing protein 4 (ATPBD4), which is consistent with the report that the amidation step of diphthamide biosynthesis is ATP-dependent (7). The analysis of the cofitness data thus pointed to the possibility that yeast YLR143W or human ATPBD4 is the diphthamide synthetase.…”
Section: Resultssupporting
confidence: 74%
“…BLAST search indicated that YLR143W is conserved in both eukaryotes and archaea, but not in bacteria, similar to other proteins involved in diphthamide biosynthesis. The human ortholog is ATP-binding domain-containing protein 4 (ATPBD4), which is consistent with the report that the amidation step of diphthamide biosynthesis is ATP-dependent (7). The analysis of the cofitness data thus pointed to the possibility that yeast YLR143W or human ATPBD4 is the diphthamide synthetase.…”
Section: Resultssupporting
confidence: 74%
“…Mutant cells defective in diphthamide biosynthesis have been selected in other laboratories by treating toxin-sensitive cells with either DT or exotoxin A. Mutants of Chinese hamster ovary (CHO) cells, isolated by Moehring and coworkers, were found to be recessive and comprised three complementation groups (30,31). Similar mutants in Saccharomyces cerevisiae, selected by exposing spheroplasts to DT, were also recessive and comprised five complementation groups (dphl, dph2, dph3, dph4, and dph5) (8).…”
mentioning
confidence: 98%
“…Diphthamide synthesis on EF2 operates through a complex pathway, which has been conserved among lower and higher eukaryotes (Chen et al, 1985;Moehring et al, 1984;Liu et al, 2004). In the budding yeast Saccharomyces cerevisiae, diphthamide biosynthesis requires at least five genes, DPH1-DPH5 (Liu et al, 2004), two mammalian homologues of which (DPH1/OVCA1 & DPH3/KTI11) are intriguingly involved in embryonic development and cell proliferation in rodents and humans (Fichtner & Schaffrath, 2002;Chen & Behringer, 2004;Fichtner et al, 2003;Liu & Leppla, 2003;Nobukuni et al, 2005;Liu et al, 2006).…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%